Regulation of p53 and survivin by Curcuma longa extract to caspase-3 dependent apoptosis in triple negative breast cancer cells - Deryne Anggia Paramita; Dedy Hermansyah; Desiree Anggia Paramita; Nur Dina Amalina (Medicinski glasnik, 2022)
Aim: Triple negative breast cancer cells (TNBC) are the population of breast cancer cells that are responsible for cancer recurrence and apoptosis resistance. Unfortunately, current therapies have limited efficacy to TNBC population due to apoptosis resistance and chemoresistance. Tumour suppressor p53 and survivin are primary targets for TNBC therapy. Consequently, a search for a natural compound which targets p53 and survivin is needed to further advance TNBC treatment. Curcuma longa extract (CL), a natural compound induces apoptosis in several cancer cells by targeting various molecules and possess fewer side effects. However, a possible potential of CL as p53- and survivin modulating agent in TNBC cells has not been investigated. Methods: MDAMB-231 cells were treated with several concentration of CL, after which, viability, p53 gene expression, surviving protein expression, and caspase-3 protein expression were evaluated. Results: After 24-h treatment, CL possessed cytotoxic effect with IC50 value of 13 ?g/mL. Treatment with 1.625, 3.25, 6.5, and 13 ?g/mL of CL resulted in 2.70-25.80% increase in caspase-3 expression levels followed by 94.60 - 21.60% decrease in survivin protein levels. CL induced remarkably p53 gene expression ratio up to 5-fold at 13 ?g/mL. Survivin protein levels were inversely proportional to p53 accumulation levels. Low survivin protein levels combined with high levels of p53 accumulation were correlated to higher apoptotic rates. Conclusion: p53 and survivin as molecular targets of CL contribute to caspase-3-dependent apoptosis in TNBC cells and this compound represents an attractive p53- and survivin modulating agent in TNBC.
Keywords: Caspase-3; Curcuma longa extract; p53; survivin; TNBC